Microplastic Removal in Wastewater Treatment Plants (WWTPs) by Natural Coagulation: A Literature Review - Taskeen Reza; Zahratul Huda Mohamad Riza; Siti Rozaimah Sheikh Abdullah; Hassimi Abu Hasan; Nur ‘Izzati Ismail; Ahmad Razi Othman (Toxics, 2023)
Urban industrialization has caused a ubiquity of microplastics in the environment. A large percentage of plastic waste originated from Southeast Asian countries. Microplastics arising from the primary sources of personal care items and industrial uses and the fragmentation of larger plastics have recently garnered attention due to their ubiquity. Due to the rising level of plastic waste in the environment, the bioaccumulation and biomagnification of plastics threaten aquatic and human life. Wastewater treatment plant (WWTP) effluents are one of the major sources of these plastic fragments. WWTPs in Southeast Asia contribute largely to microplastic pollution in the marine environment, and thus, further technological improvements are required to ensure the complete and efficient removal of microplastics. Coagulation is a significant process in removing microplastics, and natural coagulants are far superior to their chemical equivalents due to their non-toxicity and cost-effectiveness. A focused literature search was conducted on journal repository platforms, mainly ScienceDirect and Elsevier, and on scientific databases such as Google Scholar using the keywords Wastewater Treatment Plant, Coagulation, Microplastics, Marine Environment and Southeast Asia. The contents and results of numerous papers and research articles were reviewed, and the relevant papers were selected. The relevant findings and research data are summarized in this paper. The paper reviews (1) natural coagulants for microplastic removal and their effectiveness in removing microplastics and (2) the potential use of natural coagulants in Southeast Asian wastewater treatment plants as the abundance of natural materials readily available in the region makes it a feasible option for microplastic removal.